Analisis Pengendalian Internal Pengadaan Barang dan Jasa Pemerintah Pada Badan Pertanahan Nasional (BPN) Cilacap - Setyaningsih, Ratna; Nusa Perdana, Petrolis; Khairunnisa, Hera (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
This study aims to analyze internal control over the procurement cycle of government goods/services in one of the government agencies, namely the National Land Agency (BPN) Cilacap. From the implementation of the controls carried out, further analyzed its conformity with Government Regulation (PP) No. 60 of 2008 concerning the Government Internal Control System. The method used in this study is a qualitative method by conducting interviews with informants to obtain primary data and documentation to obtain secondary data. The informants in this study were a Commitment Making Officer (PPK) and a Government Employee with a Contract Agreement (PPPK) who served as the operator of SAKTI application assets. The result of this study is that the application of internal control over the procurement cycle of goods/services at BPN Cilacap has been implemented and in accordance with PP No. 60 of 2008. However, not fully internal control has been implemented because there are still sub-elements of internal control that have not been implemented.